Editorial cartoon of Homer Bunker. - Stantis:::Creator::::::::::::
Cartoon showing Homer Bunker, who attempted to get Of Mice and Men banned and impose a dress code in Memphis public schools, setting alight a copy of the book. 'Why am I proposing a dress code for County schools?...' '...Because you can't wear just anything to a book burning.' Digital copy only. No hard copy.